New horizons of DNA adductome for exploring environmental causes of cancer. Issue 1 (12th October 2020) - Totsuka, Yukari; Watanabe, Masatoshi; Lin, Yingsong
Abstract: Chemical carcinogenesis is focused on the formation of DNA adducts, a form of DNA damage caused by covalent binding of a chemical moiety to DNA. The detection of carcinogen‐DNA adducts in human tissues, along with demonstration of mutagenicity/carcinogenicity in experimental systems, and validation of adducts as biomarkers of environmental exposure and indicators of cancer risk in molecular epidemiological studies suggests a pivotal role of DNA adducts in cancer development. However, accurate measurement of DNA adducts in varied biological samples is challenging. Advances in mass spectrometry have prompted the development of DNA adductome analysis, an emerging method that simultaneously screens for multiple DNA adducts and provides relevant structural information. In this review, we summarize the basic principle and applications of DNA adductome analysis that would contribute to the elucidation of the environmental causes of cancer. Based on parallel developments in several fields, including next‐generation sequencing, we describe a new approach used to explore cancer etiology, which integrates analyses of DNA adductome data and mutational signatures derived from whole‐genome/exome sequencing. Abstract : This review article provides an overview of the developments in DNA adductome analyses, which are based on mass spectrometry and can simultaneously screen multiple DNA adducts. Moreover, we propose a newer approach to explore cancer etiology using integrated analyses of DNA adductome data and mutational signatures derived from whole‐genome/exome sequencing.